2018
DOI: 10.1101/253831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditional Upregulation of KCC2 selectively enhances neuronal inhibition during seizures

Abstract: / Summary.Efficacious neuronal inhibition is sustained by the neuronal K + Cl -co-transporter KCC2, and loss of KCC2 function through injury or mutation is associated with altered GABAergic signalling and neuronal seizures. Here we report a transgenic mouse with conditional KCC2 overexpression that results in increased membrane transport function. Increased KCC2 has little impact on behavioural and in vitro assays of neuronal excitability and GABAA receptor responses under resting conditions. In contrast, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Moore and colleagues reported a 68% lower [Cl − ] i measured through a gramicidinperforated patch clamp, 11 whereas we previously reported a 64% transport capacity increase measured through an ammonium-reporter fluorescence assay. 13 In addition, the chemoconvulsant challenge used by Moore and colleagues was more severe, with seizures developing more rapidly and progressing more readily into convulsive status epilepticus. 11 When we previously used a more-severe chemoconvulsant challenge on these same transgenic mice (+/+DoxOFF), KCC2 overexpression reduced progression into status epilepticus but did not prevent milder seizure behaviors from developing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore and colleagues reported a 68% lower [Cl − ] i measured through a gramicidinperforated patch clamp, 11 whereas we previously reported a 64% transport capacity increase measured through an ammonium-reporter fluorescence assay. 13 In addition, the chemoconvulsant challenge used by Moore and colleagues was more severe, with seizures developing more rapidly and progressing more readily into convulsive status epilepticus. 11 When we previously used a more-severe chemoconvulsant challenge on these same transgenic mice (+/+DoxOFF), KCC2 overexpression reduced progression into status epilepticus but did not prevent milder seizure behaviors from developing.…”
Section: Discussionmentioning
confidence: 99%
“…In this mouse line, 2-3-fold KCC2 overexpression occurs in pyramidal neurons 7 days after stopping dietary doxycycline supplementation, as knock-in tetracyclinecontrolled transcriptional activator (tTA) and KCC2 expression are coupled to the calcium-calmodulindependent kinase II alpha (CaMKIIα) and knock-in tTA-response element (TRE) promoters, respectively. 13 Inheritance of both tTA and TRE (+/+) or TRE alone (−/+) was determined prior to weaning through tail-tip DNA polymerase chain reaction (PCR) analysis (tTA forward/reverse primers: 5′-AGGCTTGAGATCTGGCCAT AC-3′/5′-AAGGGCAAAAGTGAGTATGGTG-3′; TRE-KCC2 forward/reverse primers: 5′-AGCAGAGCTCGTTT AGTGAACCGT-3′/5′-TGGAAACTCAAAGCGAGGAACT GC-3′). Mice were fed doxycycline-laced chow (600 mg/ kg, Gordons Specialty Feeds) from birth to suppress KCC2 F I G U R E 1 Increased KCC2 expression potentiates seizure suppression by diazepam.…”
Section: Methodsmentioning
confidence: 99%
“…Here we observed that acute anti-inflammatory treatment not only prevented KCC2 downregulation but significantly enhanced its expression in the deafferented lateral VNs. This phenomenon may induce an excitability deficit during the acute phase since KCC2 upregulation is likely associated with amplified inhibitory GABAergic transmission (Bos et al, 2013;Goulton et al, 2018;Lorenzo et al, 2020). KCC2 upregulation was also reported after SCI and administration of corticosteroids (Dai et al, 2018).…”
Section: Acute Anti-inflammatory Treatment Alters Adaptive Post-lesiomentioning
confidence: 96%
“…CaMK2 promoter can be induced by cessation of dietary supplementation with doxycycline (Goulton et al, 2018). KCC2 expression was driven by the tetracycline transactivator (tTA) binding to the tetracycline operator construct (tet-O), and this interaction is prevented by doxycycline (Gossen and Bujard, 1992).…”
Section: Used a Conditional Transgenic Mouse In Which Overexpressiomentioning
confidence: 99%
“…In mice that expressed both tet-O and tTA, overexpression of KCC2 was prevented by dietary supplementation of Dox, and triggered by cessation of Dox supplementation. Details of this transgenic mouse have been recently reported as a preprint in Goulton et al(Goulton et al, 2018), which demonstrates that Dox cessation increases KCC2 mRNA and protein expression throughout the cortex, amygdala and hippocampus.…”
mentioning
confidence: 99%